Whole-Genome Comparative Analysis Reveals Association Between Salmonella Genomic Variation and Egg Production Systems - Sodagari, Hamid Reza; Sahibzada, Shafi; Robertson, Ian; Habib, Ihab; Wang, Penghao (Frontiers in Veterinary Science, 2021)
Non-typhoidal Salmonella, particularly Salmonella enterica serovar Typhimurium (S. Typhimurium), is the predominant endemic serovar in the Australian egg production industry and is one of the most frequently reported serovars in foodborne infections in Australia. This study was conducted to investigate the genomic characteristics of Salmonella isolated from retail table eggs in Western Australia and to identify the impact of production systems on genomic characteristics of Salmonella such as virulence and antimicrobial resistance. A total of 40 non-typhoidal Salmonella isolates [S. Typhimurium isolates (n = 28) and Salmonella Infantis isolates (n = 12)] sourced from retail eggs produced by different production systems (barn-laid, cage, and free-range) in Western Australia were sequenced by whole-genome sequencing. The isolates were de novo assembled, annotated, and analyzed. The results indicated an association between Salmonella genomic variation and the system used to raise poultry for egg production (p-value < 0.05). All but one of the S. Infantis isolates were recovered from eggs collected from poultry raised under barn and cage production systems. A higher proportion (83.3%) of S. Typhimurium isolates were recovered from the eggs produced by free-range production system as compared with those produced under barn (76.9%) and cage production systems (53.3%). Our analysis indicated that Salmonella isolated from the eggs produced by barn and cage production systems had more virulence genes than the isolates of the free-range produced eggs. A low carriage of antimicrobial-resistant gene was detected in the isolates of this study. We have built a Salmonella genomics database and characteristics-linked gene pools to facilitate future study, characterization, and tracing of Salmonella outbreaks.